Analisis Faktor- Faktor Yang Mempengaruhi Terhadap Pemilihan Penolong Persalinan Di Wilayah Kerja Puskesmas Air Hitam Sarolangun Tahun 2017 - Merdekawati (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat (IAKMI) Provinsi Sumatera Selatan, 2018)
Health problem mother and childrens (KIA), like problem healt in indonesian. Indikator healt sector is mother  dead number (AKI) and dead number babys (AKB). This staff do for stop dead number mom (AKI) in indonesia between for increase service antenatal all, all facilities health services with good quality and reach all target groups, increase helping labor by force profesional by gradually, increase detection early highrisk to pregnant mother and do system references. Increase service neonatal with good quality. This result for factors influence for voter helping labor in territory working Puskesmas Black Water District Sarolangun. This result design is kuantitatif with design result make is survei analytic case control. Population this result as much 52 person. Sample this result as much 522 respondent with tecnic total sampling. Analysist data use with analysist univariat, bivariat, use test Chi-Square (a=0.005) and multivariat with use methoa regresi linier. This analysist result found for education 57,7%, working 59,6%, knowledge 59,6%, and perception 53,8% for the choice helping labor 65,4% tell that non healt. Result analysist bivariat factor education (p=0,22), working (0,012), KNOWLEDGE (P=0,025), perception (p=0,014). Result analysisit multivariat can get variabel knowledge and have a relationship between variabel education, working, knowledge and perception for choices helping labor for social healt ready.